BIOMECHANICAL RATIONALE OF AN EARLY DENTURE CHOISE IN PROSTHETICS OF BOUNDED DEFECTS OF DENTAL ROWS - R.V. Petrenko; A.H. Fenko; A.I. Petrenko; K.V. Marchenko; V.N. Dvornik; A.P. Pavlenko; V.D. Kindii (Український стоматологічний альманах, 2018)
The work is focused on the study of the stress-strain state of support tissue in a fragment of the lower dental row in case of prosthetic of a defect bounded by the canine and the first molar with removable bridge prostheses that have various design features to justify the choice of the most rational denture design.